Digitalisation medical records: improving efficiency and reducing burnout in healthcare - Shaharul, Nur Adibah; Ahmad Zamzuri, Mohd ‘Ammar Ihsan; Ariffin, Ahmad Azuhairi; Azman, Ahmad Zaid Fattah; Mohd Ali, Noor Khalili (Multidisciplinary Digital Publishing Institute, 2023)
(1) Background: electronic medical record (EMR) systems remain a significant priority for the improvement of healthcare services. However, their implementation may have resulted in a burden on healthcare workers (HCWs). This study aimed to determine the prevalence of burnout symptoms among HCWs who use EMRs at their workplace, as well as burnout-associated factors. (2) Methods: an analytical cross-sectional study was conducted at six public health clinics equipped with an electronic medical record system. The respondents were from a heterogeneity of job descriptions. Consent was obtained before enrolment into the study. A questionnaire was distributed through an online platform. Ethical approval was secured. (3) Results: a total of 161 respondents were included in the final analysis, accounting for a 90.0 response rate. The prevalence of burnout symptoms was 10.7 (n = 17). Three significant predictors were obtained in the final model: experiencing ineffective screen layouts and navigation systems, experiencing physical or verbal abuse by patients, and having a poor relationship with colleagues. (4) Conclusions: the prevalence of burnout symptoms among healthcare workers working with electronic medical record systems was low. Despite several limitations and barriers to implementation, a paradigm shift is needed to equip all health sectors with electronic medical record systems to improve healthcare service delivery. Continuous technical support and financial resources are important to ensure a smooth transition and integration.